IMPLEMENTATION OF GOOGLE CLASSROOM AS MEDIA IN ELEMENTARY SCHOOL TEACHER EDUCATION UNIVERSITAS PASUNDAN - Rahmiati, Devi; Permana, Jaka; Indriani, Rina; Almujab, Saiful; Maryani, Leni (Universitas Pahlawan Tuanku Tambusai, 2019)
The aim this research are the using of google classroom as media learning students of Elementary School Teacher Education at Universitas Pasundan. The use of media in learning is very important to achieved the explicit learning objectives in lesson design that have been made by lecturers. This study to get an overview in third semester of Academic Year 2018/2019 which are applied to the Learning Strategy subject in elementary school. The research method is quasi-experimental with analysis data used a paired t test with SPSS program versi 21.0 for window. Subjects is a students of PGSD semester III in Class D, amounting to 30 people. The implementation of this research is in the form of a cycle consisting of plan, do, and see. Based on data analysis, the results is thitung = 22,122 > ttable = 1,699, then H0 rejected and H1 accepted. It can be concluded that there are significant the used google classroom media in Learning Strategies subject in student Elementary School Teacher Education at Universitas Pasundan are carried out in accordance with the stages of plan, do, and see. The existence of these stages challenges the lecturers to design learning as interesting as possible so that the quality and results of the learning process will increase and demand that the lecturers continue to innovate learning in order to support the improvement of their professionalism as educators